The medieval town of Koilyk: written sources and archaeological research - Taleev, Д.А.; Moldakhmet, A.A.; Apasheva, С.Н. (Turkic Studies Journal, 2026)
The article considers the historical development of archaeological exploration of the medieval town of Koilyk (known in written sources as Koilyk, Pulad) located in the northeastern Zhetisu region. Koilyk was one of the most important political, economic and cultural centers along the Great Silk Road in the Middle Ages. The study offers a comprehensive analysis of written sources and archaeological materials, thereby determining the role and significance of the town in the regional historical context. Particular attention is devoted to the accounts of the European traveler and French envoy Guillaume de Rubruck, who traveled to Mongolia through the Zhetisu region in the thirteenth century. His records constitute an important source for the study of medieval Koilyk, providing valuable information about the town as a major commercial center and describing the ethnic and religious diversity of its population. The article also reviews the scholarly perspectives of both domestic and foreign researchers, including V.V. Bartold, A.N. Bernshtam, M. Tynyshbayev, K.M. Baipakov. Their interpretations concerning the location and historical significance of Koilyk are comparatively analyzed. Archaeological evidence confirms that the site of Koilyk corresponds to the settlement of Antonovka, located in the eastern part of the village of Koilyk in the Sarkant district of the Almaty region. Systematic excavations conducted since 1998 have made it possible to reconstruct the internal structure of the city. The citadel, shahristan, and rabad were identified, and the urban layout was established. Excavations revealed the remains of various religious structures, demonstrating that Islam, Buddhism, and Manichaeism coexisted in Koilyk. In particular, the locations of a mosque, a Buddhist temple, a Manichaean church, and a Sufi khanqah were identified. In addition, public and residential buildings – including bathhouses, mausoleums, residential buildings and economic complexes, and new data were obtained on the social structure of the town. Since 2004, within the framework of the state program “Cultural Heritage”, archaeological research has intensified, allowing for a more detailed study of the cultural layers of the site. These investigations have clarified the role of Koilyk not only within the Zhetisu region but also within broader international trade networks. Archaeological finds included both locally produced goods and imported items from China and Iran. Coins (tenge) minted in Koilyk were also discovered, indicating the town’s extensive economic connections and the high level of development of crafts and trade. Overall, the article provides a comprehensive assessment of the significance of Koilyk in the processes of urbanization and in the cultural and economic development of medieval Zhetisu.